Uterus Weight of Ovariectomized Rats Given Cocoa Powder and Extract - Ariza Budi Tunjung; Misnawi Jati; Pratiwi Pudjiastuti; Afaf Baktir (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2017)
Estrogen is a hormone that influences the growth of uterus. Ovariectomized rats lose their ovaries as the main source of estrogen so their uterus tends to shrink. The objective of thise study was to evaluate the potency of cocoa as an estrogen substitute, which was done through an experiment that tested the influence of cocoa products on the uterus weight of ovariectomized rats. There were five treatments and in each of the treatments, six wistar rats were given the substance for three days. Four groups of treatment consisted of ovariectomized rats given cocoa extract (875.2 ppm of polyphenols, 1 g/kg of body weight, BW), cocoa powder (369.8 ppm of polyphenols, 1 g/kg BW), olive oil (10 mL/kg BW), or estradiol valerate (1 mg/kg BW). The fifth group consisted of intact (non-ovariectomized) rats given 10 mL/kg BW of water. The finding showed that the ovariectomized rats given olive oil had lower uterus weight than that of intact rats, while the ovariectomized rats given estradiol valerate had higher uterus weight compared to the intact and olive oil groups. The ovariectomized rats given cocoa powder and extract had higher uterus weight compared to those given only olive oil; although they were not significantly different. Correlation between the body weight and uterus weight varied across treatment groups. The rats given olive oil showed significant, positive correlation, while the intact rats showed moderate, positive correlation. The rats given estradiol valerate and cocoa powder showed non-significant correlation. Since the polyphenol content in cocoa powder was at lower concentration than that in the cocoa extract, it was predicted that cocoa polyphenols are more potential in the lower concentration. This study concludes that even though consumption of cocoa powder and extract did not significantly induced uterus growth, cocoa is still considered having estrogenic activity by lowering the correlation between the body weight and uterus weight in ovariectomized rats.